MOTOR VEHICLE SAFETY DISTANCES USING THE SENSOR ULTRASONIC MICROCONTROLLER AT89S51 - Eka Nofa; Nenny Anggraini., SKom, MT Nenny Anggraini., SKom, MT (Jurnal Sistem Komputer, 2009)
In writing that I make with the title "MOTOR VEHICLE SAFETY DISTANCES USING THE SENSOR ultrasonic microcontroller AT89S51." Meant to reduce the number of motor vehicle accidents, especially for four-wheeled vehicle about to take place every day are happening every day. This happens because not all vehicles have a range of vehicle security system that serves as a warning, if the distance of their vehicles too close to another vehicle. This tool will be placed at the front bunper which will alert you if the distance a vehicle is too close to the vehicle in front.